Nurses’ Best Friend? The Lived Experiences of Nurses Who Utilized Dog Therapy in the Workplace - Valerie A. Esposito Kubanick; Joy Z. Scharfman (Nursing Reports, 2025)
The aim of this work is to explore and understand the lived experience of nurses who chose to schedule visits with an Emotional Support Animal (ESA), i.e., a dog, during their working shift. Background/Objectives: Nursing practice is rigorous, weighted with intense responsibility that creates an environment conducive to stress and anxiety for the nurses, who have reported a higher level of work stress than other healthcare professionals. Knowing and addressing the factors impacting mental health/nurses’ well-being is crucial to providing care to patients. Stressful work environments result in burnout, compassion fatigue, depression, anxiety, suicide, and resignation. Understanding nurses’ perspectives on work related stress encourages hospitals to structure practices supporting nurses’ mental health and ability to provide quality care. Methods: A qualitative hermeneutic phenomenological approach was employed. Participants scheduled six weekly 10-min visits with Rex, a certified Service Dog for anxiety depression and PTSD, and registered ESA. A sample of 11 RNs participated in Rex visits at the workplace; field notes were taken during observations of visits. Semi-structured 30-min interviews conducted via Zoom, audio-recorded, and transcribed with NVivo were conducted. Results: Data were examined with Interpretative Phenomenological Analysis. Four main themes emerged: Preparing for the unknown, Doing the work, Refueling and resetting-Visits with Rex, What about nurses? Conclusions: This study highlights the need for nurses and hospital systems to incorporate self-care/self-reflection, including time/opportunities for nurses’ stress management during their practice. Knowledge of nurses receiving ESA interventions sheds light on how to protect/preserve the well-being of nurses practicing in this demanding profession. ESAs for nurses in the workplace offers an option to utilize dog therapy to re-energize and continue their shift renewed and refreshed.